The search for conjugative transposon in rumen bacterium Prevotella bryantii Bsub1 4 - Gorenc, Gregor (Acta agriculturae Slovenica, 2009)
Only few plasmids and bacteriophages have been described to date in ruminal prevotella strains, therefore it appears plausible that the genetic exchange in these organisms must exploit other routes. Large conjugative transposons make possible the gene exchange process in bacteria from the genus Bacteroides, the phylogenetic relatives of ruminal prevotellas. The access to fully or partially finished genome sequences of Bacteroides and Prevotella representatives made possible the search for conserved regions within putative conjugative transposons. Multiple sequence alignment of known and putative conjugative transposon gene sequences of Bacteroides thetaiotaomicron, Prevotella intermedia, Bacteroides fragilis and Tanerella sp. was used to locate partially conserved regions within most preserved conjugative transposition genes, traG, and to construct appropriate degenerated oligonucleotide primers. These were used to amplify genome fragments from ruminal prevotella strains. Sequence analysis of the subcloned PCR products revealed the presence of a hypothetical gene in the genome of Prevotella bryantii B14, similar to the ORF BF2880 from B. fragilis YCH46, which is a part of a large conjugative transposon. Inverse PCRs were designed and performed to confirm the initial findings. A partial map of P. bryantii B14 putative conjugative transposon region was constructed, indicating an intergeneric horizontal gene transfer.
Keywords: microbiology; mikrobiologija; bacteria; bakterije; vamp; molekularna genetika; konjugativni transpozon